PENGUKURAN TINGKAH LAKU PADA MODEL NYERI NEUROPATIK PERIFER TIKUS DENGAN CCI CHRONIC CONSTRICTION INJURY - Hanik Badriyah Hidayati,* Paulus Sugianto,* Junaidi Khotib,** Chrismawan Ardianto,** Kuntoro,*** Moh (NEURONA, 2018)
PAIN OCCURS IN 20 OF PATIENTS WITH CHRONIC PAIN THIS MAINLY DUE TO THE LACK OF EFFECTIVE TREATMENT AND THE PRESENCE OF DRUGS SIDE EFFECTS ANIMAL MODELS HAVE BEEN BROADLY UTILIZED IN VALIDATING THE THERAPEUTIC TARGET AND THE DEVELOPMENT OF ANALGESIC DRUGS CHRONIC CONSTRICTION INJURY CCI IS A MODEL OF PERIPHERAL NEUROPATHIC PAIN CHARACTERIZED BY ALLODYNIA AND HYPERALGESIA